PENGARUH LIKUIDITAS, PERTUMBUHAN PENJUALAN DAN KEBIJAKAN DEVIDEN TERHADAP HARGA SAHAM PADA PERUSAHAAN CONSUMER GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA - Windari Ade Fransiska; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to test partially and simultaneously the influence of liquidity, salesgrowth and dividend policy on stock prices. Where independent variable in this research isliquidity, sales growth and dividend policy and while the dependent variable is stock price. Thesample used is secondary data derived from the financial statements of consumer goodscompanies listed on the Indonesia Stock Exchange (BEI) in 2010 until 2014.This study uses secondary data from the company's financial statements. Sampling usingcensus techniques. Data analysis using multiple linear regression analysis, t test, F test, and testof coefficient of determination. Data analysis using multiple linear regression analysis withSPSS 20.The results of this study indicate that partial liquidity variable (t test) has a positive andsignificant effect on stock prices, while sales growth and dividend variables negatively affectstock prices in consumer goods companies listed on the Indonesia Stock Exchange.Simultaneous test results (F) show the influence of liquidity variables, sales growth and dividendpolicy on stock prices on consumer goods companies listed on the Indonesia Stock Exchange.Keywords: liquidity, sales growth, dividend policy and stock price